Living under the sun : examination of Proverbs and Qoheleth - Frydrych, Tomáš, 1969- (Supplements to Vetus Testamentum, 2002)
The difficulties that biblical wisdom literature poses to the theologian are caused not only by its distinctiveness from other biblical traditions, but also by the internal tensions within it. The present book seeks to explore the nature and causes of these tensions. The study carries out comprehensive comparison of the worldviews represented by Proverbs and Qoheleth, and the worlds that these reflect, looking at the aims and methods of their quest, their epistemologies, theological and cosmological perspectives, and their anthropological and social views. The conclusion of the enquiry throws new light on the dynamics of the tension between thewe two books, questioning whether standard methods of Old Testament theology can do justice to the wisdom tradition, and at the same time, opening the door for new theological approaches to be devised.